Examining the Attitudes and Problem Solving Skills of Physical Education and Sports Students - Feray Özbal, Ayşe; Balıbey, Kerim; Meral, Ali; Alıç, Sinan (Horizon Research Publishing Co., Ltd., 2019)
This study was conducted to explore attitudes and problem solving skills of physical training and sports students. The participants of the study were 260 students (111 female and 149 male) attending Kastamonu University School of Physical Training and Sports. The data collection tools used in the study were personal information form prepared by the researchers, Scale of Attitudes of Preservice Teachers Towards Teaching Profession, whose validity and reliability studies were conducted (1) and Problem Solving Inventory, which was developed (2) and adapted to Turkish language (2). The analyses revealed no significant difference for “gender”, “age”, “family income level”, and “class level” variables; however, a significant difference was found for the variable “educational background of parents”. In addition, simple linear correlation analysis of the scores of attitude and problem solving dimensions showed a low level of meaningful relationship (r=.028, p<.001).
Keywords: 4. Education